A Pragmatic Analysis Of Commissive Utterance In The Wizard Of Oz Movie Manuscript - Nidak, Muslihatun, Drs. H. Maryadi, M.A, Dra. Dwi Haryanti, M.Hum (2013)
The objectives of this study are: (1) to identify the forms of commissive utterance used in The Wizard of Oz movie manuscript, (2) to describe the implicature of commissive utterance used in The Wizard of Oz movie manuscript, and (3) to describe the politeness patterns of commissive utterance used in The Wizard of Oz movie manuscript. The type of this research is descriptive qualitative research. The object of this study is commissive utterance in The Wizard of Oz movie manuscript. In collecting the data, the writer uses documentation. There are three steps to collect data, namely: the writer reads the movie manuscript, then the writer selects the commissive utterances in The Wizard of Oz by underlining the dialogues which contain commissive utterances then collects them, and the last the writer codes the data that are in the forms of words, phrases, and sentences which have correlation with commissive utterance in the movie manuscript. The collected data are analyzed by using Frank theory of types of sentences, Grice theory of implicature, FTA's theory of politeness patterns. The results of the research show that: (1) the forms of commissive utterances are, declarative sentence (50%), interrogative sentence (30%), imperative sentence (17,5%), and exclamatory sentence (2,5%). (2) There are two kinds of implicature, namely conventional implicature, including offer (17,5%), volunteering (5%), promising (27,5%), refusing (5%), forbidden (7,5%), and also conversational implicature, including promise (5%), swear (15%), threat (5%), and warning (12,5%). (3) The politeness patterns of commissive utterance are bald on record (25%), positive politeness (60%), negative politeness (10%), and off-record strategy (5%).